Carbon dioxide capture via aqueous N-methyldiethanolamine (MDEA)-1-butyl-3-methylimidazolium acetate (bmimAc) hybrid solvent - Hailegiorgis, S.M. (American Institute of Physics Inc., 2017)
In this study, aqueous hybrid solvents from a mixture of aqueous N-methyldiethanolamine (MDEA) and 1-butyl-3-methylimidazolium acetate, bmimAc as ionic liquids (ILs) were formulated at different mass ratio. In each aqueous hybrid solvents, the concentrations of MDEA were kept constant at 30 wt%. In the hybrid solvents, the solubility of CO2 was investigated at bmimAc concentration of 10 wt% and 20 wt%, respectively and results were compared with pure aqueous MDEA solvent. It was observed that the solubility of CO2 is significantly improved in the hybrid solvent as compared to the solubility of CO2 in pure aqueous MDEA solvent. However, increasing the concentration of bmimAc from 10 wt% to 20 wt% has a negative effect on the solubility of CO2 due to viscosity effect. It was also observed that hybrid solvents with 10 wt% bmimAc has better CO2 loading capacity. Increasing pressure from 10 bar to 20 bar has demonstrated an increase in CO2 absorption capacity as well as CO2 absorption rate. Hybrid solvents prepared from amine and imidazolium ILs will be a promising solvent in the capturing of CO2. © 2017 Author(s).